The Conference of Medellín: political and ecclesial context and its position on Education and Youth - Siqueira, Giseli do Prado (Horizonte, 2018)
The Second General Conference of the Latin American Episcopate, held in Medellin, Colombia, between August 24 and September 6, 1968, produced an important and significant document - The Medellin Conclusions - which recorded the positions of the Church of Latin America, assuming a liberating position against oppression in the continent. The purpose of Pope Paul VI, as the title of the Conference proposal says, was to enable a reading of Latin American reality in the light of the Second Vatican Council. The bishops did more than that: they read the Council in the light of Latin American reality. Within this context, this article intends, from a bibliographical research, to present some elements of the political and ecclesial reality of Medellin and to analyze two aspects of the document: the education and youth. The 1960s, and particularly the year 1968, are historic, effervescent moments in the context of the Cold War, thus impacting many changes. The Church clearly takes the work of insertion into poor communities. Education is considered in a liberating perspective, there is the insertion of religious in the base ecclesial communities. Catholic youth, on the other hand, assume social and political commitments. In Medellin the Latin American Church gains its own identity and an original way of doing theology, liberation theology and its option for the poor. The exercise of collegiality also takes important steps, including in the form of drafting the document. Therefore, the celebration of the 50 years of this document should have a focus on its values and limitations and recover its advances, thus contributing to the debate in the field of the Sciences of Religion.